PERBAIKAN MUTU PADA PROSES DAN PRODUKSI SPUN-PILE DENGAN MENGGUNAKAN METODE TAGUCHI - Gideon Hadi Kusuma; Ferryanto S.G.; Dedy Cahyono H (Civil Engineering Dimension, 1999)
There are two major problems in producing concrete spun piles. First is the concrete strength and second is the uniformity of the cross section. Due to spinning, most concrete spun piles cross section consist of two layers. The inner part which is mortar with high water and cement content and the outer layer, which is quite dense with aggregate. Due to this different layer with different shrinkage properties concrete spun piles are prone to crack. This shrinkage cracks can cause corrosion on the prestressed wire thus influencing its durability. This research was done to find the best design to give a product with the thinnest layer of mortar while achieving the strength (K 500). The Taguchi design of experiment method, a method to improve the quality of a product by minimizing the effect caused by variation without eliminating the causes, is used. The control factors chosen are Sand Aggregate (S/A) ratio, admixture, speed and duration of spinning, each with 3 levels. The simulated noise chosen is gradation of sand with 2 different levels. Eighteen (18) experiments are needed for the above simulated noise and control factor. Through the Signal to Noise Ratio (SNR) and variance analysis, can be proposed a robust design which is less sensitive to the noise factors as well as giving better result from the previous product condition Abstract in Bahasa Indonesia : Keberhasilan melaksanakan proyek konstruksi tepat pada waktunya adalah salah satu tujuan terpenting, baik bagi pemilik maupun kontraktor. Keterlambatan adalah sebuah kondisi yang sangat tidak dikehendaki, karena akan sangat merugikan kedua belah pihak dari segi waktu dan biaya. Penelitian ini bertujuan menemukan faktor-faktor yang sangat berperan atau mendominasi sebagai penyebab keterlambatan, dengan maksud agar proses perencanaan dan penjadwalan proyek konstruksi dapat dilakukan dengan lebih lengkap dan cermat; sehingga keterlambatan sedapat mungkin dihindarkan atau dikendalikan. Temuan penyebab-penyebab keterlambatan, yang dikonfirmasikan dengan sigi lapangan menggunakan kuesioner yang didistribusikan kepada kontraktor, menunjukkan bahwa masalah-masalah tidak seksamanya rencana kerja, tidak tersedianya sumber daya dan kurangnya komunikasi/koordinasi, merupakan faktor-faktor yang dominan sebagai penyebab keterlamabatan dari sisi kontraktor. Dari sisi pemilik proyek, masalah ketidaklengkapan dan ketidakjelasan desain dan lingkup pekerjaan, masalah sistim pengawasan dan pengendalian proyek, merupakan faktor yang dominan sebagai penyebab keterlambatan